Enhancement of norisoprenoid and acetoin production for improving the aroma of fermented mango juice by Bacillus subtilis-HNU-B3. (February 2022) - Cai, Chengchen; Zhang, Ming; Chen, Haiming; Chen, Wenxue; Chen, Weijun; Zhong, Qiuping
Graphical abstract: Highlights: Bacillus subtilis -HNU-B3 increased the antioxidant activity of fermented mango-juice. Norioprenoids and acetoin affected the favor of fermented mango juice. Bacillus subtilis -HNU-B3 is a promising alternative for mango-juice fermentation. Abstract: Mango juice (MJ) has high nutritional value and decent flavor. However, its aroma could be easily changed by heat treatment during processing, which affects its acceptability and quality. In this study, Bacillus subtilis -HNU-B3 that could transfer carotenoid, was obtained from orchard soil to improve the aroma of fermented mango juice (FMJ). Compared with MJ, the organic acid content of FMJ by B. subtilis -HNU-B3 was significantly changed, and the contents of succinic acid and malic acid were increased to 3.68 mg/mL and 2.04 mg/mL, respectively. Moreover, volatile compounds identified by headspace solid-phase micro-extraction gas-phase mass spectrometry in FMJ were norisoprenoid and acetoin, accounting for 51.52 % of the total volatile substances. In addition, B. subtilis -HNU-B3 fermentation significantly increased the antioxidant capacity and total phenol contents of MJ, and the activity of carotenoid cleavage dioxygenase was 188 U/L. In conclusion, the aroma of FMJ could be improved by B. subtilis -HNU-B3 through increasing the content of norisoprenoid and acetoin. Our results provide theatrical support for Bacillus subtilis to improve the aroma quality of FMJ.